Antioxidant enzyme changes in response to osmotic stress in wheat (Triticum aestivum L.) seedling - Naderi, Rana; Valizadeh, Mostafa; Toorchi, Mahmoud; Shakiba, Mohammad Reza (Acta Biologica Szegediensis, 2014)
In order to evaluate the effects of osmotic stress on behavioral responses of antioxidant enzymes including superoxide dismutase (SOD), peroxidase (POX), catalase (CAT), glutathione reductase (GR) and ascorbate peroxidase (APX), a factorial experiment was carried out under laboratory conditions with three groups of wheat genotypes (tolerant, intermediate and susceptible) and three osmotic stress levels induced by PEG (control, mild and severe). Electrophoretic analyses were performed for three antioxidant enzymes SOD, POX and CAT in shoots of wheat seedlings using 7.5% slab polyacrylamide gels. The activities of GR and APX were determined spectrophotometrically. For SOD, POX and CAT, two, seven and one isozymes were observed, respectively. Statistical analysis showed that osmotic stress has a significant effect on enzymatic activities in wheat seedlings. POX, CAT, GR and APXactivities were increased significantly in the severe stress compared with control condition about 31, 61, 129 and 149 percent, respectively. Whereas, SOD activity increased significantly by 41% in the mild stress compared with control treatment. The highest enzymatic activity was belonged to tolerant group under severe stress conditions for almost all of isozymes and enzymes. Among the antioxidant enzymes, APX activity was increased most drastically in severe stress condition. The extent of damage to the wheat seedlings seems to depend on genotype and severity of osmotic stress.